Asuhan Keperawatan pada Tn. S dengan Post Operasi Benigna Prostate Hyperplasia di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Riko Feli Alfakon; Ahmad Zakiudin; Sukirno Sukirno (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Benign Prostatic Hyperplasia (BPH) is a condition characterized by enlargement of the prostate gland, resulting from the proliferation of non-cancerous cells. The condition mostly affects older men, significant for men whose prevalence increases with age. Prostate hyperplasia is a health problem in people aged 50 years and older, leading to a decline in their quality of life. The World Health Organization (WHO) informs that there are 70 million cases of degenerative diseases including conditions such as Benign Prostatic Hyperplasia (BPH). In developed countries, BPH is found in 19% of the population, while in developing countries, the prevalence is 5.35% (Ritonga, 2022).